The Role of Village Heads in Motivating Drug Users in Palong Village, Pidie Regency - Armiwal; Thaib, Anwar; Ramadhani, Syahrul (Dinasti International Journal of Digital Business Management, 2023)
In an effort to obtain provisions for drug users who have the motivation not to return to their "habitat", this study is expected to find answers to the positive possibilities of the motivation itself. Based on the facts above, the author is interested in conducting research on "The Role of Keuchik in Reducing the Number of Addictions of Drug Users in Gampong Palong, Pidie Regency". The objectives to be achieved from this study are: To find out and explain the role of Keuchik in motivating drug users to reduce addiction in Gampong Palong, Pidie Regency, and to find out what efforts are made by drug users to reduce drug addiction. In this study, the researcher used a qualitative approach, considering that in this study the researcher intended to obtain an overview of the Role of Keuchik in Reducing the Number of Addictions of Drug Users in Gampong Palong, Pidie Regency, so it was carried out with field research, namely research conducted in the field directly to obtain the required data. So, field research or field research is carried out concerning problems or life in real reality, not abstract thoughts contained in written or recorded texts and documents.